Liquidation World : On the Art of Living Absently - Kukuljevic, Alexi (Book collections on Project MUSE., 2017)
In ' Liquidation World', Alexi Kukuljevic examines a distinctive form of subjectivity animating the avant-garde: that of the darkly humorous and utterly disoriented subject of modernity, a dissolute figure that makes an art of its own vacancy, an object of its absence. Shorn of the truly rotten illusion that the world is a fulfilling and meaningful place, these subjects identify themselves by a paradoxical disidentification -- through the objects that take their places. They have mastered the art of living absently, of making something with nothing. Traversing their own morbid obsessions, they substitute the nonsensical for sense, the ridiculous for the meaningful. Kukuljevic analyzes a series of artistic practices that illuminate this subjectivity, ranging from Marcel Duchamp's Three Standard Stoppages to Charles Baudelaire's melancholia.0He considers the paradox of Duchamp's apparatus in the Stoppages and the strange comedy of Marcel Broodthaers's relation to the readymade; the comic subject in Jacques Vache and the ridiculous subject in Alfred Jarry; the nihilist in Paul Valery's Monsieur Teste; Oswald Wiener's interpretation of the dandy; and Charles Baudelaire as a happy melancholic.